Analysis of the trends in burden of meningitis in China from 1990 to 2021, and projections until 2036 - Xu, Xi; Xu, Kai; Wu, Qiulin (Frontiers in Public Health, 2025)
BackgroundThis study aimed to describe the temporal trends in age and sex burdens of meningitis in China from 1990 to 2021 and to compare them with the global burden of the disease.MethodsUsing data from the Global Burden of Disease (GBD) 2021, this study analyzed the features of meningitis burden in China and globally, including incidence, prevalence, mortality, disability-adjusted life years (DALYs), age-standardized incidence rate (ASIR), age-standardized rates of mortality (ASMR), age-standardized rates of prevalence (ASPR), and age-standardized DALY rate (ASDR). The average annual percentage change (AAPC) and associated 95% confidence interval (95% CI) were computed using Joinpoint. A comprehensive comparative analysis of the differences in meningitis burden between China and the world was conducted from multiple dimensions, including age, sex, and periods. Using the BAPC and INLA software tools to perform a Bayesian Age-Period-Cohort (BAPC) analysis in R.ResultsFrom 1990 to 2021, the ASIR fell from 66.565/100,000 to 31.649/100,000 globally, and from 30.833/100,000 to 5.791/100,000 in China. The ASPR decreased from 11,291,266/100,000 to 92.251/100,000 globally, and from 140.1/100,000 to 16.622/100,000 in China. The ASMR decreased from 7.416/100,000 to 2.947/100,000 globally, while decreased from 3.537/100,000 to 0.475/100,000 in China. The ASDR decreased from 551.176/100,000 to 208.565/100,000 globally, while decreased from 267.304/100,000 to 27.952/100,000 in China. The global AAPC of ASIR, ASPR, ASMR, and ASDR was −2.364, 2.679, −2.970%, and −3.131%, whereas in China it was −5.307, −6.665%, −6.311%, and −7.149, respectively. The effects of age and sex on the burden of meningitis were different. Men had higher incidence and mortality rates of meningitis than women. ASIR in males and females would decrease in the following years.ConclusionThere was a discernible decline in the incidence, prevalence, mortality, and DALYs associated with meningitis in China and worldwide between 1990 and 2021. Meningitis is more common and fatal in infants and early children, followed by the older adult. Men are more likely than women to die from meningitis and to contract it. It is anticipated that the disease burden of meningitis will continue to decline over the ensuing 12 years. Meningitis continues to be a significant public health concern in China due to the country’s huge and aging population.